2005
DOI: 10.4141/a04-079
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus status of lactating dairy cows fed total mixed rations containing 0.24% vs. 0.36% phosphorus

Abstract: . W. 2005. Phosphorus status of lactating dairy cows fed total mixed rations containing 0.24% vs. 0.36% phosphorus. Can. J. Anim. Sci. 85: 409-412. The effect of dietary P content on P balance was evaluated using 14 lactating dairy cows fed a corn silage based total mixed ration (TMR) containing either 0.24% P or 0.36% P. The animals were paired by calving date at dry-off with one cow from each pair randomly assigned to either dietary treatment. All cows were fed a common TMR containing 0.34% P prepartum, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…This was surprising because decreases in BW have only been reported in dairy cows fed very low dietary P, 0.24% P compared with cows fed diets ranging in P from 0.28 to 0.42% (Valk and Sebek 1999). Cows supplemented with P at 0.42% had higher (P < 0.05) faecal P than cows on the 0.35% P diet, in agreement with previous studies, which have shown that faecal P increases as dietary P increases (e.g., Morse et al 1992;Shore et al 2005). McCaskill (1990) suggested that endogenous faecal P was one of the most important pathways responsible for almost 80% of P leaving the animal.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This was surprising because decreases in BW have only been reported in dairy cows fed very low dietary P, 0.24% P compared with cows fed diets ranging in P from 0.28 to 0.42% (Valk and Sebek 1999). Cows supplemented with P at 0.42% had higher (P < 0.05) faecal P than cows on the 0.35% P diet, in agreement with previous studies, which have shown that faecal P increases as dietary P increases (e.g., Morse et al 1992;Shore et al 2005). McCaskill (1990) suggested that endogenous faecal P was one of the most important pathways responsible for almost 80% of P leaving the animal.…”
Section: Resultssupporting
confidence: 89%
“…The apparent digestibility of P and P balance have been calculated for dairy cows (Martz et al 1990;Spiekers et al 1993;Valk et al 2002), although methods of measurements differ among experiments. When potentially absorbable P is provided in sufficient amounts or in excess, dairy cows appear to have the ability to absorb the amount of P needed Shore et al 2005;Ekelund et al 2006). Efficiency of absorption of P declines as intake of P increases in cattle (Challa et al 1989) and in sheep (Field et al 1977).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This database subset comprised data from lactating dairy cows from 25 studies (Martz et al, 1990;Morse et al, 1992;Spiekers et al, 1993;Delaquis and Block, 1995;Khorasani et al, 1997;Knowlton et al, 2001Wu et al, 2001Wu et al, , 2003Knowlton and Herbein, 2002;Guyton et al, 2003;Kebreab et al, 2005;Kincaid et al, 2005;Shore et al, 2005;Wu, 2005;Ekelund et al, 2006;Kamiya et al, 2006a;Knowlton et al, 2007;Dann et al, 2008;Moreira et al, 2009;Myers and Beede, 2009;Taylor et al, 2009;Van Straalen et al, 2009;Herrera et al, 2010;Puggaard et al, 2011) and included 130 treatment means. The response variable of interest was P excretion in the feces, both in grams per day and as a fraction of P intake.…”
Section: Databasementioning
confidence: 99%
“…This database subset contained 94 treatment means from 19 studies (Martz et al, 1990;Spiekers et al, 1993;Delaquis and Block, 1995;Knowlton et al, 2001Knowlton and Herbein, 2002;Valk et al, 2002;Guyton et al, 2003;Borucki Castro et al, 2004;Kincaid et al, 2005;Peterson et al, 2005;Roche et al, 2005;Shore et al, 2005;Kamiya et al, 2006b;Odongo et al, 2007;Dann et al, 2008; Table 2.…”
Section: Databasementioning
confidence: 99%